Salmonella enterica Diversity in Central Californian Coastal Waterways - Walters, Sarah P. (American Society for Microbiology, 2013)
Salmonella enterica is one of the most important bacterial enteric pathogens worldwide. However, little is known about its distribution and diversity in the environment. The present study explored the diversity of 104 strains of Salmonella enterica isolated over 2 years from 12 coastal waterways in central California. Pulsed-field gel electrophoresis (PFGE) and multilocus sequence typing were used to probe species diversity. Seventy-four PFGE patterns and 38 sequence types (STs) were found, including 18 newly described STs. Nineteen of 25 PFGE patterns were indistinguishable from those of clinical isolates in PulseNet. The most common ST was consistent with S. enterica serovar Typhimurium, and other frequently detected STs were associated with the serovars Heidelberg and Enteritidis; all of these serovars are important etiologies of salmonellosis. An investigation into S. enterica biogeography was conducted at the level of ST and subspecies. At the ST and subspecies level, we found a taxon-time relationship but no taxon-area or taxon-environmental distance relationships. STs collected during wet versus dry conditions tended to be more similar; however, STs collected from waterways adjacent to watersheds with similar land covers did not tend to be similar. The results suggest that the lack of dispersal limitation may be an important factor affecting the diversity of S. enterica in the region.